Brazing method for metal-ceramic composite material and metal in argon environment
By using a low-cost muffle furnace to braze metal-ceramic composite materials and metals in an argon environment, the problems of poor wettability of the solder and high vacuum brazing cost are solved, and high mechanical properties and low cost welding are achieved. Effect.
Patent Information
- Application Number
- CN202411668587.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
Prior Art When connecting metal-ceramic composite materials and metals, the wettability of the solder on the ceramic surface is poor, and it is difficult to react with the ceramic. The vacuum brazing cost is high, and non-vacuum brazing can easily lead to oxidation of the solder, affecting the welding quality. .
The brazing method of metal-ceramic composite materials and metals is adopted in an argon environment, and the brazing is performed using a muffle furnace with low equipment costs to ensure that the solder is reacted and connected to the base material under an argon environment.
The high mechanical properties of the brazed joint are achieved, the average shear strength is above 70MPa and the maximum shear strength is 141.5MPa, which reduces welding costs and ensures the stability of welding quality.
Smart Images

Figure CN119501224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal-ceramic composite materials and metal brazing, and in particular to a brazing method of a metal-ceramic composite material and metal in an argon environment. Background Art
[0002] Metal-ceramic composites have the toughness, high thermal conductivity and good thermal stability of metals, as well as the high temperature resistance, corrosion resistance and wear resistance of ceramics. They are widely used in cutting tools, high-temperature structural parts in the aerospace industry, industrial pipe linings and other fields. However, due to its poor toughness and high brittleness, it is difficult to make large and complex components on the one hand, and its ability to resist thermal stress and impact loads during single use is poor on the other hand. If metal-ceramic composites can be welded with metals to obtain structural parts with the excellent properties of both materials, it will be helpful to solve the common problems faced by metal-ceramic composites, extend their service life, and further expand their application areas. It has important significance and broad application prospects.
[0003] At present, the most common method for connecting metal-ceramic composites and metals is brazing. Brazing connection has the advantages of reliable connection joints and good repeatability. However, the use of brazing to connect metal-ceramic composites and metals faces many challenges, one of which is the poor wettability of the brazing material on the ceramic surface. Therefore, it is necessary to invent a process method to improve the wetting of the brazing material on ceramics or ceramic-based composites and promote the interfacial reaction between the metal-ceramic composite material and the brazing material. The Chinese patent with application number CN113084287A introduces a non-vacuum brazing method for plasma cutting electrodes, which coats a metal layer on the surface of the hafnium wire, and prefabricates a solder sheet and a flux in the center hole of the copper substrate, and then assembles the hafnium wire with a metal layer on the surface and the copper substrate together, and fills with inert gas for welding, which provides a method for brazing metal materials with protection using inert gas. However, the bonding type between the ceramic phase and the metal in the metal-ceramic composite is different. It is difficult for ordinary brazing filler metal to react with and wet the ceramic phase. The properties of active brazing filler metal are affected by the oxygen partial pressure. It is very easy to oxidize at high temperature and lose its activity. Therefore, the brazing of metal-ceramic composite materials and metals is mostly done by vacuum brazing. However, vacuum brazing furnaces are expensive and the welding cost is high. In a non-vacuum environment, the brazing material is easy to oxidize. Generally, short-time heating is used to reduce the oxidation of the materials to be welded. For example, Li Xianfen et al. used flame brazing to connect metals and metal-ceramic composite materials (Li Xianfen, Xu Daorong, Liu Ning, et al. Experimental study on flame brazing of Ti(C,N)-based metal ceramics and 45 steel [J]. Hard Alloys, 2003, (02): 94-97.), and Zhu Haixu et al. used high-frequency induction brazing of hard alloys and steel (Zhu Haixu, Yu Weiyuan. Development of a new brazing paste for brazing hard alloy layer of diamond drill bit and steel [J]. Hot Working Technology, 2018, 47 (07): 204-208.). However, flame brazing has low efficiency, is easy to pollute the environment, and is easy to burn the parent material, resulting in unstable welding quality; and high-frequency induction brazing is difficult to accurately control the welding temperature, and it is difficult to accurately formulate process parameters according to the actual joint structure regulation and stress relief requirements. Therefore, it is necessary to invent a process method that can reduce the welding cost while ensuring the stable connection quality of the weldment so that the joint strength of the weldment meets the application requirements.
[0004] In view of the above problems, the present invention innovatively proposes a method for brazing metal-ceramic composite materials and metals in an argon environment. The brazing is performed using a muffle furnace with low equipment cost. The difference from the vacuum brazing method is that the equipment cost is lower, and argon is continuously introduced during the brazing process. The brazing material reacts and connects with the base material (the base material refers to metal and metal-ceramic composite materials, and the base material is a commercially available material) in an argon environment. The difference from flame brazing or high-frequency induction brazing is that this method can achieve the brazing connection of metal-ceramic composite materials without damaging the materials to be welded; at the same time, the process parameters can be accurately controlled according to process requirements. The metal-ceramic composite material and metal brazing joint prepared by this method has no obvious defects in the microstructure, excellent mechanical properties, an average shear strength of more than 70MPa, and a maximum shear strength of 141.5MPa. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for brazing a metal-ceramic composite material and a metal in an argon environment in view of the above-mentioned deficiencies in the prior art.
[0006] A method for brazing a metal-ceramic composite material and a metal in an argon environment, characterized in that it comprises the following steps:
[0007] (1) Remove oxide film and impurities from metal-ceramic composite materials and metal surfaces, clean and dry them;
[0008] (2) uniformly coating the brazing filler metal on the upper surface of the metal in step (1), then stacking the metal-ceramic composite material in step (1) on the brazing filler metal, and then placing a pressing block on the upper surface of the metal-ceramic composite material to obtain a material to be welded;
[0009] (3) Place the materials to be welded in step (2) into a muffle furnace, then slowly introduce argon gas to start the brazing process of the muffle furnace.
[0010] Preferably, the metal-ceramic composite material is one of ZrC-W and TiC-Ni, the metal is one of GH3128 high-temperature alloy and 304 stainless steel, and the brazing material is one of 30AgCuZn solder paste, a mixture of 30AgCuZn solder paste and QJ102 brazing flux, and a mixture of 30AgCuZn alloy powder and QJ102 brazing flux.
[0011] Preferably, the pressing block is made of alumina.
[0012] Preferably, in step (1), the metal-ceramic composite material is polished with a grinding wheel, then ultrasonically cleaned with anhydrous ethanol, and finally rinsed with running water and blown dry; 400# and 800# sandpaper are used to polish the metal, then ultrasonically cleaned with anhydrous ethanol, and finally rinsed with running water and blown dry.
[0013] Preferably, the mixture of 30AgCuZn solder paste and QJ102 flux is a uniform mixture, wherein the mass proportion of 30AgCuZn solder paste is 80%-100%, and the mass proportion of QJ102 flux is 0-20%; the mixture of 30AgCuZn alloy powder and QJ102 flux is a uniform mixture, wherein the mass proportion of 30AgCuZn alloy powder is 80%-100%, and the mass proportion of QJ102 flux is 0-20%.
[0014] Preferably, in step (2), the coating amount of the solder is 0.01 g / mm 3 .
[0015] Preferably, in step (3), the muffle furnace brazing procedure is: heating to 680-1100°C at a rate of 1-50°C / min, maintaining for 1-40min, then cooling to 400°C at a rate of 1-20°C / min, and finally naturally cooling to 150°C with the muffle furnace.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The brazing process of the present invention is simple, has low requirements on equipment, and is low in cost. It is suitable for large-scale industrial production and application, has broad application prospects, and ensures the stability of welding quality while reducing costs.
[0018] (2) The present invention improves the reaction between the solder and the base material in an argon environment and is environmentally friendly. It can effectively improve the mechanical properties of the brazed joint. The brazed joint has no obvious defects in its structure, the average shear strength is above 70 MPa, and the maximum shear strength reaches 141.5 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a macroscopic image of the brazed joint provided in Example 1 of the present invention.
[0020] Figure 2 This is a SEM image of the brazing joint interface provided by Example 2 of the present invention.
[0021] Figure 3 This is a SEM image of the brazing joint interface provided by Example 4 of the present invention.
[0022] Figure 4 This is a macroscopic image of the brazed joint provided in Example 5 of the present invention. DETAILED DESCRIPTION
[0023] The purpose of the present invention is to provide a method for brazing a metal-ceramic composite material and a metal in an argon environment. The preparation method provided by the present invention has a simple process, effectively reduces the welding cost, and improves the mechanical properties of the joint.
[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments and comparative examples in the present invention, all other embodiments and comparative examples obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Without departing from the spirit or essential features of the present invention, the present invention will be further described in conjunction with embodiments.
[0026] The present invention provides a method for brazing a metal-ceramic composite material and a metal in an argon environment, which adopts the following technical scheme and includes the following steps:
[0027] (1) Remove oxide film and impurities from metal-ceramic composite materials and metal surfaces, clean and dry them;
[0028] (2) uniformly coating the brazing filler metal on the upper surface of the metal in step (1), then stacking the metal-ceramic composite material in step (1) on the brazing filler metal, and then placing a pressing block on the upper surface of the metal-ceramic composite material to obtain a material to be welded;
[0029] (3) Place the materials to be welded in step (2) into a muffle furnace, then slowly introduce argon gas to start the brazing process of the muffle furnace.
[0030] Further, the metal-ceramic composite material is one of ZrC-W and TiC-Ni, the metal is one of GH3128 high temperature alloy and 304 stainless steel, and the brazing material is one of 30AgCuZn solder paste, a mixture of 30AgCuZn solder paste and QJ102 brazing flux, and a mixture of 30AgCuZn alloy powder and QJ102 brazing flux. In implementation, both the solder paste and the brazing flux are commercially available materials.
[0031] Furthermore, the material of the pressing block is alumina material. In practice, the pressing block can be made of commercial high temperature resistant alumina ceramic material.
[0032] Furthermore, in the step (1), the metal-ceramic composite material is polished with a grinding wheel, then ultrasonically cleaned with anhydrous ethanol, and finally rinsed with running water and blown dry; 400# and 800# sandpaper are used to polish the metal, then ultrasonically cleaned with anhydrous ethanol, and finally rinsed with running water and blown dry.
[0033] Furthermore, the mixture of 30AgCuZn solder paste and QJ102 flux is a uniform mixture, in which the mass proportion of 30AgCuZn solder paste is 80%-100%, and the mass proportion of QJ102 flux is 0-20%; the mixture of 30AgCuZn alloy powder and QJ102 flux is a uniform mixture, in which the mass proportion of 30AgCuZn alloy powder is 80%-100%, and the mass proportion of QJ102 flux is 0-20%.
[0034] Furthermore, in step (2), the coating amount of the solder is 0.01 g / mm 3 .
[0035] Furthermore, in step (3), the muffle furnace brazing procedure is: heating to 680-1100°C at a rate of 1-50°C / min, maintaining for 1-40min, then cooling to 400°C at a rate of 1-20°C / min, and finally naturally cooling to 150°C in the muffle furnace.
[0036] Embodiment 1:
[0037] The metal is GH3128 high-temperature alloy with a size of 15mm×15mm×3mm, and the metal-ceramic composite material is ZrC-W composite material with a size of 4mm×4mm×4mm. The GH3128 high-temperature alloy and ZrC-W composite material are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5 minutes. After drying, they are stacked from bottom to top in the order of GH3128 high-temperature alloy / commercial 30AgCuZn solder paste / ZrC-W composite material. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace without argon gas, and the program is started to start brazing. The temperature is raised to 830℃ at a heating rate of 20℃ / min, kept at this temperature for 10 minutes, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. Please refer to Figure 1 , the results showed that the two materials failed to connect and the shear strength could not be obtained.
[0038] Embodiment 2:
[0039] The metal is GH3128 high temperature alloy with a size of 15mm×15mm×3mm, and the metal-ceramic composite material is ZrC-W composite material with a size of 4mm×4mm×4mm. The GH3128 high temperature alloy and ZrC-W composite material are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5 minutes. After drying, they are stacked from bottom to top in the order of GH3128 high temperature alloy / commercial 30AgCuZn solder paste / ZrC-W composite material. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace, and then argon is slowly introduced to start the brazing program. The temperature is raised to 830℃ at a heating rate of 20℃ / min, kept at this temperature for 10min, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. The shear strength of the brazed joint tested by a universal tensile machine is 75.8MPa.
[0040] Embodiment 3:
[0041] The metal is GH3128 high temperature alloy with a size of 15mm×15mm×3mm, and the metal-ceramic composite material is ZrC-W composite material with a size of 4mm×4mm×4mm. The GH3128 high temperature alloy and ZrC-W composite material are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5 minutes. After drying, they are stacked from bottom to top in the order of GH3128 high temperature alloy / commercial 30AgCuZn solder paste / ZrC-W composite material. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace, and then argon is slowly introduced to start the brazing program. The temperature is raised to 850℃ at a heating rate of 20℃ / min, kept at this temperature for 10min, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. The shear strength of the brazed joint tested by a universal tensile machine is 86.5MPa.
[0042] Embodiment 4:
[0043] The metal is GH3128 high temperature alloy with a size of 15mm×15mm×3mm, and the metal-ceramic composite material is ZrC-W composite material with a size of 4mm×4mm×4mm. The GH3128 high temperature alloy and ZrC-W composite material are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5 minutes. After drying, they are stacked from bottom to top in the order of GH3128 high temperature alloy / commercial 30AgCuZn solder paste + QJ102 flux mixture / ZrC-W composite material. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace, and then argon is slowly introduced to start the brazing program. The temperature is raised to 850℃ at a heating rate of 20℃ / min, kept at this temperature for 10min, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. The shear strength of the brazed joint tested by a universal tensile machine is 141.5MPa.
[0044] Embodiment 5:
[0045] The metal is GH3128 high-temperature alloy with a size of 15mm×15mm×3mm, and the metal-ceramic composite material is ZrC-W composite material with a size of 4mm×4mm×4mm. The GH3128 high-temperature alloy and ZrC-W composite material are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5 minutes. After drying, they are stacked from bottom to top in the order of GH3128 high-temperature alloy / commercial 30AgCuZn powder / ZrC-W composite material. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace, and then argon is slowly introduced to start the brazing program. The temperature is raised to 830℃ at a heating rate of 20℃ / min, kept at this temperature for 10 minutes, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. Please refer to Figure 2 , the results showed that the two materials failed to connect and the shear strength could not be obtained.
[0046] Embodiment 6:
[0047] The metal is GH3128 high temperature alloy with a size of 15mm×15mm×3mm, and the metal-ceramic composite material is ZrC-W composite material with a size of 4mm×4mm×4mm. The GH3128 high temperature alloy and ZrC-W composite material are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5min. After drying, they are stacked from bottom to top in the order of GH3128 high temperature alloy / commercial 30AgCuZn powder+QJ102 flux mixture / ZrC-W composite material. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace, and then argon is slowly introduced to start the brazing program. The temperature is raised to 830℃ at a heating rate of 20℃ / min, kept at this temperature for 10min, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. The shear strength of the brazed joint tested by a universal tensile machine is 48.6MPa.
[0048] Embodiment 7:
[0049] The metal is GH3128 high temperature alloy of 15mm×15mm×3mm, and the metal-ceramic composite material is TiC-Ni metal ceramic of 5mm×5mm×5mm. The GH3128 high temperature alloy and TiC-Ni metal ceramic are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5min. After drying, they are stacked from bottom to top in the order of GH3128 high temperature alloy / commercial 30AgCuZn solder paste / TiC-Ni metal ceramic. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace, and then argon is slowly introduced to start the brazing program. The temperature is raised to 800℃ at a heating rate of 20℃ / min, kept at this temperature for 10min, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. The shear strength is tested by a universal tensile machine and is 56.07MPa.
[0050] Embodiment 8:
[0051] The metal is 15mm×15mm×3mm 304 stainless steel, and the metal-ceramic composite material is 5mm×5mm×5mm TiC-Ni metal ceramic. The 304 stainless steel and TiC-Ni metal ceramic are polished with sandpaper and grinding wheel respectively, and then ultrasonically cleaned in anhydrous ethanol for 5 minutes. After drying, they are stacked in the order of 304 stainless steel / commercial 30AgCuZn solder paste / TiC-Ni metal ceramic. The coating volume of the brazing material is 5×5×0.5mm. The pressing block is placed in the muffle furnace, and then argon is slowly introduced to start the brazing program. The temperature is raised to 800℃ at a heating rate of 20℃ / min, kept at this temperature for 10min, and then cooled to 400℃ at a cooling rate of 5℃ / min, and then naturally cooled to 150℃ with the furnace, and the furnace is opened for sampling. The shear strength is tested by a universal tensile machine and is 63.67MPa.
[0052] Summary: In an argon protection environment, commercial 30AgCuZn solder paste or commercial 30AgCuZn solder paste + QJ102 flux mixture or commercial 30AgCuZn alloy powder + QJ102 flux mixture was used as the brazing material to achieve the brazing connection between metal-ceramic composite materials (ZrC-W, TiC-Ni) and metals (GH3128 nickel-based alloy, 304 stainless steel);
[0053] See also Figure 1 and Figure 2 , the difference between Example 1 and Example 2 is whether argon is introduced during brazing. It can be found that when argon is not introduced, the brazing material undergoes serious oxidation and blackening, and the connection between the two materials is not achieved. After argon is introduced, the interface organization shows a good reaction, and the brazing seam is composed of light gray (Ag) and dark gray (Cu, Ni). At the same time, a small amount of W element in ZrC-W is dissolved into the brazing seam to form white (W). The brazing material organization is tightly combined with the parent materials on both sides, and there are no obvious cracks in the brazing seam and the joint interface. Through mechanical property testing, the joints brazed with argon have good shear strength, reaching more than 45MPa, and the maximum shear strength is 141.5MPa;
[0054] By using a muffle furnace with low equipment cost for brazing experiments, the cost is greatly reduced compared to traditional vacuum brazing furnaces; and compared to other methods such as flame brazing and high-frequency induction brazing, compared with flame brazing, argon gas is always kept in, and the gas in the furnace has been evacuated before the experiment, so no CO2 gas or other impurity gas will be generated during the brazing process, which is environmentally friendly and pollution-free. No harmful or polluting gas will be generated during welding, and no damage such as ablation will occur. Compared with high-frequency induction brazing, the process parameters can also be accurately controlled by program settings;
[0055] contrast Figure 2-Figure 4It can be seen that adding an appropriate amount of QJ102 flux to the brazing material (the mass proportion of QJ102 flux in the brazing material is 0-20%) can promote the reaction between the brazing material and the base material. More dark gray (Cu, Ni) is generated on the side of the ZrC-W composite material, indicating that the addition of the flux promotes the dissolution of the brazing material to the nickel-based high-temperature alloy, and more nickel elements enter the brazing seam to participate in the reaction; by comparing Example 3 and Example 4, it can be obtained that the joint strength is significantly improved after adding the QJ102 flux. By comparing Example 5 and Example 6, it can be found that when 30AgCuZn powder is used alone as the brazing material, the powder is not melted and the two base materials cannot be connected. When QJ102 flux is added and mixed with 30AgCuZn powder, the brazing connection of the two base materials is successfully achieved. Examples 3, 7, and 8 illustrate that this method is not limited to specific materials, and can also be applied to the connection of different metal-ceramic composite materials with different metals. This method provides an example verification for the non-vacuum brazing of metal-ceramic composite materials and metals.
[0056] The above only expresses the preferred embodiments of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications, improvements and substitutions can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for brazing a metal-ceramic composite material and a metal in an argon environment, characterized in that: The following steps are involved: (1) Remove oxide film and impurities from metal-ceramic composite materials and metal surfaces, clean and dry them; (2) uniformly coating the brazing filler metal on the upper surface of the metal in step (1), then stacking the metal-ceramic composite material in step (1) on the brazing filler metal, and then placing a pressing block on the upper surface of the metal-ceramic composite material to obtain a material to be welded; (3) Place the materials to be welded in step (2) into a muffle furnace, then slowly introduce argon gas to start the brazing process of the muffle furnace.
2. The method for brazing a metal-ceramic composite material and a metal in an argon environment according to claim 1, characterized in that: The metal-ceramic composite material is one of ZrC-W and TiC-Ni, the metal is one of GH3128 high-temperature alloy and 304 stainless steel, and the brazing material is one of 30AgCuZn solder paste, a mixture of 30AgCuZn solder paste and QJ102 brazing flux, and a mixture of 30AgCuZn alloy powder and QJ102 brazing flux.
3. The method for brazing a metal-ceramic composite material and a metal in an argon environment according to claim 1, characterized in that: The material of the pressing block is alumina.
4. The method for brazing a metal-ceramic composite material and a metal in an argon environment according to claim 1, characterized in that: In the step (1), the metal-ceramic composite material is polished with a grinding wheel, then ultrasonically cleaned with anhydrous ethanol, and finally rinsed with running water and blown dry; 400# and 800# sandpaper are used to polish the metal, then ultrasonically cleaned with anhydrous ethanol, and finally rinsed with running water and blown dry.
5. The method for brazing a metal-ceramic composite material and a metal in an argon environment according to claim 1 or 2, characterized in that: The mixture of 30AgCuZn solder paste and QJ102 flux is a uniform mixture, wherein the mass proportion of 30AgCuZn solder paste is 80%-100%, and the mass proportion of QJ102 flux is 0-20%; the mixture of 30AgCuZn alloy powder and QJ102 flux is a uniform mixture, wherein the mass proportion of 30AgCuZn alloy powder is 80%-100%, and the mass proportion of QJ102 flux is 0-20%.
6. The method for brazing a metal-ceramic composite material and a metal in an argon environment according to claim 1, characterized in that: In the step (2), the coating amount of the solder is 0.01 g / mm 3 .
7. The method for brazing a metal-ceramic composite material and a metal in an argon environment according to claim 1, characterized in that: In step (3), the muffle furnace brazing procedure is: heating to 680-1100°C at a rate of 1-50°C / min, maintaining for 1-40min, then cooling to 400°C at a rate of 1-20°C / min, and finally naturally cooling to 150°C in the muffle furnace.
Citation Information
Patent Citations
Non-vacuum brazing method of plasma cutting electrode
CN113084287A